Instytucjonalny i organizacyjny rozwój średnich szkół ogólnokształcących w województwie gdańskim po II wojnie światowej (1945–1948) - Gorloff, Elżbieta (Biuletyn Historii Wychowania, 2014)
After World War II, high schools in the Gdansk region had to be built virtually from scratch. However, it is evident there were some major differences between the new and old districts, where the schools’ tasks went beyond teaching. Their role was to integrate local communities and give them a sense of stability. The former secondary school districts began their activities on the basis of pre-war organisational structures, and were established very quickly, almost immediately after the war ended. However, the network of grammar schools in new counties formed much more slowly, although in the 1945/46 school year there was already a secondary school in each county town. The intensity of the development of secondary schools can be shown in numbers. In the 1944/1945 school year, 14 secondary schools were established, and a year later there were already 28. With the development of institutional schools, their organisational development followed. Within a year, the number of students nearly trebled. Quickly, though not as strongly, there was an increase in the number of teachers. The major breakthrough for these institutions was 1948, in which, by decision of the school and party authorities, Poland experienced the reorganisation of general school education.